Dinamika Gerakan Sosial Gafatar (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2018)
Gafatar is a form of community upheaval in Indonesia in the current reformed era. Issues surrounding the ideology and the attempts of treason case became the problem that caused Gafatar to lose the masses of the public. Gafatar has the concept of food self-sufficiency that is then implemented in a peasant movement as its criticism of the government. To explain the dynamics of the Gafatar social movement, this work used McAdam et al theories about Political Opportunities, Mobilizing Structures, and Cultural Framings. The political opportunity arises from the distrust of government programs that have been offered to the people who are deemed ineffective. Mobilizing structures of Gafatar movement is manifested through the formation of the organization, forming a network of cooperation, and collective action. While cultural framing, created through the issues addressed to Gafatar causing the formation of negative stigma in society.